FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN BIDAN TERHADAP PENERAPAN STANDAR OPERASIONAL PROSEDUR (SOP) PELAYANAN ANTENATAL CARE - Septerina Purwandani Winarso; Pamungkas Puji Rahayu; Sumiyati Sumiyati (POLTEKKES KEMENKES SEMARANG, 2019)
In providing midwifery services, it must be in accordance with established standards, namely referring to all quality requirements of health services and equipment to meet the needs of the community. Midwife compliance with ANC service standards is influenced by several factors. This study aims to find factors related to midwives' compliance with 2019 antenatal care standard operating procedures (SOPs). The type of research used is correlational analytics. The population is all midwives who work in Jatilawang Health Center and Rawalo Health Center. The sample in this study was 44 midwives. The results showed the majority of midwives aged 21-35 years (52.3%), educated in D3 Midwifery (93.2%), had 11-20 years of service (47.7%). 100% ANC service infrastructure complete. There is no relationship between age (p value 0.323), education (p value 1.00), years of service (p value 0.471), and infrastructure and midwife compliance with standard operational procedures (SOP) for antenatal care services. The conclusion of this study there is no relationship between age, education, years of service, and infrastructure with midwife compliance with standard operational procedures (SOP) for antenatal care services.